Impact of Fintech on Work From Home & Mobile Banking Operations: Evidence From Islamic Banking Sector During Covid-19 in Sri Lanka - Nuskiya Hassan; AP. Misrina (Garuda Prestasi Nusantara Consulting, 2021)
FinTech is an emerging modern financial industry that has used and utilized innovative technology to improve its activities and it has taken the world by storm. Anyone anywhere can access and perform their tasks from their convenient couch by simply doing few touches with their fingertips on their smartphones. The purpose of this research is to analyze the impact of FinTech on Work From Home (WFH) & Mobile banking operations of the Islamic banking sector during COVID-19. The Pandemic has frozen the whole world stands still and affected people's life particularly the medium of communication, Lifestyle, health, and wealth. Hence, Citizens around the world had no choice than following the lockdown rules and accepting Curfew laws implemented by the government Even though the people who had these devices faced problems accessing their online banking activities. Therefore, Islamic banks faced various issues and challenges while implementing FinTech during COVID 19. The study was done with a qualitative survey based on the primary data collection technique. Therefore, the data were collected from 38 sample responses (Al-Falah 5, Amana Bank 27, and HNB 6). Thus, data analysis is done through the software of SPSS and the findings show that, descriptive and inferential statistics with standard data presentation tools such as reliability test of the instrument and data, correlation analysis, and regression analysis and a sample test for hypothesis testing. Accordingly, the study was recommended, the bank can be at a great place in encouraging and influencing people to be great at using technology in WFH and mobile banking operations. If the banks have introduced technology into banking activities, people will be required to use it by default. This will encourage people to be innovative in using this technology, Banks can introduce technology in pawning money transactions and Bank E-cheque been introduced in Sri Lanka, there will be increases in more numbers of business and commercial money transactions.